Pregnancy outcomes in women with repeated implantation failures after intracytoplasmic morphologically selected sperm injection (IMSI) - Oliveira, Joao Batista A. [UNESP]; Cavagna, Mario; Petersen, Claudia G. [UNESP]; Mauri, Ana L.; Massaro, Fabiana C.; Silva, Liliane F. I. [UNESP]; Baruffi, Ricardo L. R.; Franco, Jose G. [UNESP] (Biomed Central Ltd., 2011)
Background: The purpose of this study was to compare laboratory and clinical outcomes of intracytoplasmic morphologically selected sperm injection (IMSI) and conventional intracytoplasmic sperm injection (ICSI) in couples with repeated implantation failures.Methods: A total of 200 couples with at least two prior unsuccessful ICSI cycles were enrolled: 100 couples were submitted to IMSI and 100 were submitted to routine ICSI. For IMSI, spermatozoa were selected at 8400x magnification using an inverted microscope equipped with Nomarski (differential interference contrast) optics. For conventional ICSI, spermatozoa were selected at 400x magnification. Clinical outcomes were evaluated between the two groups.Results: Study patients were comparable in age, number of treatment failures, aetiology of infertility, percentage of normal form assessed by MSOME (motile sperm organelle morphology examination), semen parameters, total number of oocytes collected, number of mature oocytes collected, total number of embryos transferred and number of high-quality embryos transferred. No statistically significant differences between the two groups were observed with regard to rates of fertilisation, implantation and pregnancy/cycle. Although not statistically significant, rates of miscarriage (IMSI:15.3% vs ICSI:31.7%), ongoing pregnancy (IMSI:22% vs ICSI:13%) and live births (IMSI:21% vs ICSI:12%) showed a trend towards better outcomes in the IMSI group. In addition, analysis of subpopulations with or without male factor showed similar results.Conclusions: Our results suggest that IMSI does not provide a significant improvement in clinical outcome compared to ICSI, at least in couples with repeated implantation failures after conventional ICSI. However, it should be noted that there were clear trends for lower miscarriage rates (approximate to 50% reduced) and higher rates of ongoing pregnancy and live births (both nearly doubled) within the IMSI group. Further confirmation as well as randomized large-scale trials are needed to confirm the beneficial effects of IMSI in couples with poor reproductive prognoses.